Flights of passage : reflections of a World War II aviator - Hynes, Samuel, 1924- (New York : F.C. Beil ; Annapolis : Naval Institute Press, 1988)
Recounts the experiences of learning to fly and of becoming a Marine bomber pilot in the Pacific during WW II.
Keywords: Hynes, Samuel, -- 1924-; United States. -- Navy -- Biography; World War, 1939-1945 -- Campaigns -- Pacific Area; World War, 1939-1945 -- Aerial operations, American; World War, 1939-1945 -- Personal narratives, American; Fighter pilots -- United States -- Biography